Devonian palynoevents in the circum-Arctic region - Marshall, John E.A.; Mangerud, Gunn; Bringué, Manuel; Bujak, Jonathan (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2022)
Devonian strata of the present-day Arctic contain abundant and diverse assemblages of terrestrial palynomorphs, particularly from Middle and Upper Devonian sections; few intervals of Lower Devonian and Silurian strata have been palynologically studied, and these demonstrate strong palynofloral similarities across the region. Based on published records, we present a compilation of six last occurrence events (LOs), 44 first occurrence events (FOs) and one acme event that have proven of value in correlation in the present-day Arctic. Although their chronostratigraphic resolution is relatively low, and a scarcity of independent age control hampers precise age assignments, palynology is the only biostratigraphic discipline available for confident chronostratigraphic correlation of most Arctic Devonian strata.